(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
In this paper, the authors shall make an effort to find answers for the issue of the applicability of the international humanitarian law in case of biological (bacteriological) war, the history of warfare and the history of diseases which are unboundedly intertwined. The biological warfare as a weaponry uses the bacteria, the viruses and other organisms that cause illnesses and other toxins that may be found in nature, having an aim to kill, disable and seriously damage the combat capabilities of the enemy. It is forbidden, according to the common international law, as well as different international agreements, to use biological agents in an armed conflict since it is considered a war crime. The implementation of the international humanitarian law as part of the international law that unifies the international and legal instruments which are applied in cases of armed conflicts so as to limit the consequences from the same, is a question for which the international community and the states pay special attention. However, what is to be questioned are the possibilities to apply the international humanitarian law in case of a biological war. The author reckons that with all the emphasis that has been addressed to the cyber warfare in the last 3 (three) to 4 (four) years, the weapon for mass destruction is seemed to be a bit forgotten.